Ground-based contrail observations: comparisons with reanalysis weather data and contrail model simulations - J. Low; R. Teoh; J. Ponsonby; E. Gryspeerdt; M. Shapiro; M. E. J. Stettler (Atmospheric Measurement Techniques)
Observations of contrails are vital for improving our understanding of the contrail formation and life cycle, informing models, and assessing mitigation strategies. Here, we developed a methodology that utilises ground-based cameras for tracking and analysing young contrails (< 35 min) formed under clear-sky conditions, comparing these observations against reanalysis meteorology and simulations from the contrail cirrus prediction model (CoCiP) with actual flight trajectories. Our observations consist of 14 h of video footage recorded over 5 different days in Central London, capturing 1582 flight waypoints from 281 flights. The simulation correctly predicted contrail formation and absence for around 75 % of these waypoints, with incorrect contrail predictions occurring at warmer temperatures than those with true-positive predictions (7.8 K vs. 12.8 K below the Schmidt–Appleman criterion threshold temperature). When evaluating contrails with observed lifetimes of at least 2 min, the simulation's correct prediction rate for contrail formation increases to over 85 %. Among all waypoints with contrail observations, 78 % of short-lived contrails (observed lifetimes < 2 min) formed under ice-subsaturated conditions, whereas 75 % of persistent contrails (observed lifetimes > 10 min) formed under ice-supersaturated conditions. On average, the simulated contrail geometric width was around 100 m smaller than the observed (visible) width over its observed lifetime, with the mean underestimation reaching up to 280 m within the first 5 min. Discrepancies between the observed and simulated contrail formation, lifetime, and width can be associated with uncertainties in reanalysis meteorology due to known model limitations and sub-grid-scale variabilities, contrail model simplifications, uncertainties in aircraft performance estimates, and observational challenges, among other possible factors. Overall, this study demonstrates the potential of ground-based cameras to create essential observational and benchmark datasets for validating and improving existing weather and contrail models.